A fundamentação de expedientes épico-dialéticos nos seminários de dramaturgia do teatro de arena de São Paulo nos anos de 1958 a 1961 - Monteiro, Letícia Silva [UNESP] (2016)
The dramaturgy seminars of Teatro de Arena from São Paulo means a moment of fundamental transformations in the thought and theater practice in the city of São Paulo and nationally. Starting from a conception of national and popular which aims the formation of new Brazilian writers through de systematic practice of discussion on aesthetic theory, theatral writings and presentation of open authoral works, subjected to debates and collaborative production. It's outbreak, in 1958 and it's development until 1961, gave origin to plays which, for the first time in Brasil, will resort epic-dialectic expedients. Between the theater plays that arose from this process, two will be analyzed: Chapetuba Futebol Clube written by Oduvaldo Vianna Filho and Revolução na América do Sul written by Augusto Boal.